1994
DOI: 10.1021/tx00042a018
|View full text |Cite
|
Sign up to set email alerts
|

Lauric acid as a model substrate for the simultaneous determination of cytochrome P450 2E1 and 4A in hepatic microsomes

Abstract: In vitro techniques have been utilized to investigate the microsomal enzymes involved in the metabolism of lauric acid and to establish conditions in which it can be used as a model substrate for both cytochrome P450 4A and cytochrome P450 2E1 in human liver microsomes. Studies of enzyme kinetics of lauric acid omega-hydroxylation in human liver microsomes indicated the involvement of more than one enzyme in this pathway, a relatively low Km enzyme with a Km of 22 microM +/- 12 (n = 8) and a high Km enzyme wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 27 publications
6
22
0
Order By: Relevance
“…This substrate can also undergo -1-hydroxylation, preferentially carried out by CYP2E1 (Clarke et al, 1994). In the present study, CYP4A1 mRNA was only found in the liver.…”
Section: Downloaded Fromsupporting
confidence: 38%
“…This substrate can also undergo -1-hydroxylation, preferentially carried out by CYP2E1 (Clarke et al, 1994). In the present study, CYP4A1 mRNA was only found in the liver.…”
Section: Downloaded Fromsupporting
confidence: 38%
“…Standard assays were used to measure the activities of P450 isoenzymes in human liver microsomes and to investigate the effect of dabigatran etexilate, dabigatran, BIBR 951 CL, and BIBR 1987 SE on the various test reactions. CYP1A1 and CYP1A2 activity was measured by phenacetin O-deethylation (Tassaneeyakul et al, 1993), CYP2C19 and CYP2B6 by S-mephenytoin 4Ј-hydroxylation (Wedlund and Wilkinson, 1996) and N-dealkylation (Heyn et al, 1996), respectively, CYP2C9 by tolbutamide hydroxylation (Ludwig et al, 1998), CYP2D6 by bufuralol 1Ј-hydroxylation (Yamazaki et al, 1994), CYP2E1 and CYP4A11 by lauric acid 11-and 12-hydroxlation, respectively (Clarke et al, 1994;Amet et al, 1995), and CYP3A by nifedipine oxidation (Guengerich et al, 1986) and testosterone 6␤-hydroxylation (modified from the technique of Newton et al, 1995). All the incubations were performed in duplicate.…”
Section: Hplc Of Dabigatran and Metabolites In Incubatesmentioning
confidence: 99%
“…Standard assays were used to measure the activities of P450 isoenzymes in human liver microsomes and to investigate the effect of linagliptin on the various test reactions. Activities of CYP1A1 and CYP1A2 were measured by phenacetin O-deethylation (Tassaneeyakul et al, 1993); CYP2A6 was measured by by coumarin 7-hydroxylation (Pelkonen et al, 2000); CYP2C19 and CYP2B6 were measured by S-mephenytoin 4Ј-hydroxylation (Wedlund and Wilkinson, 1996) and N-dealkylation (Heyn et al, 1996), respectively; CYP2C8 was measured by by paclitaxel 6␣-hydroxylation (Cresteil et al, 1994); CYP2C9 was measured by tolbutamide hydroxylation (Ludwig et al, 1998); CYP2D6 was measured by bufuralol 1Ј-hydroxylation (Yamazaki et al, 1994); CYP2E1 and CYP4A11 were measured by lauric acid 11-and 12-hydroxylation, respectively (Clarke et al, 1994;Amet et al, 1995); and CYP3A was measured by nifedipine oxidation (Guengerich et al, 1986), testosterone 6␤-hydroxylation (modified from the technique of Newton et al, 1995), and midazolam 1-hydroxylation (Gorski et al, 1994). All incubations were performed in duplicate.…”
Section: Downloaded Frommentioning
confidence: 99%